2016
DOI: 10.1021/acs.orglett.6b00047
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Catalyzed Regioselective Hydroheteroarylation of Pentafulvenes

Abstract: A diverse approach toward the catalytic regioselective nucleophilic addition of nitrogen heterocycles to Lewis acid activated pentafulvenes has been established. The developed protocol introduces pentafulvenes as nonsymmetrical alkenes for the hydroheteroarylation reaction, providing alkylidenecyclopentenylation at the C-3 position of indoles and the C-2 position of pyrrole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…A wide range of transition metals were used for this purpose. Very recently, our group established an exceptional strategy toward the regioselective hydroheteroarylation of pentafulvenes with various indoles 292 and pyrrole in the presence of a Lewis acid (Scheme ). This protocol does not need dry solvents or inert atmospheres, and readily occurs at ambient temperature. This is the first report on the endo selective 1,2-addition of a nucleophile to fulvene catalyzed by a Lewis acid.…”
Section: Miscellaneous Reactions Of Pentafulvenesmentioning
confidence: 99%
“…A wide range of transition metals were used for this purpose. Very recently, our group established an exceptional strategy toward the regioselective hydroheteroarylation of pentafulvenes with various indoles 292 and pyrrole in the presence of a Lewis acid (Scheme ). This protocol does not need dry solvents or inert atmospheres, and readily occurs at ambient temperature. This is the first report on the endo selective 1,2-addition of a nucleophile to fulvene catalyzed by a Lewis acid.…”
Section: Miscellaneous Reactions Of Pentafulvenesmentioning
confidence: 99%
“…On the basis of this unusual reactivity, we presumed that a double hydro(hetero)arylation of pentafulvene might occur if the amount of indole was doubled. In the initial monitoring, the reaction afforded the double heteroarylation product ( 3bb , 12 %) along with the monosubstituted indole ( 4bb , 75 %, Scheme ) . Various spectroscopic analyses clearly indicated that the product formed was the cyclopentenylated bisindole.…”
Section: Resultsmentioning
confidence: 99%
“…of N ‐methylindole ( 2a ) with 2 mol‐% of Cu(OTf) 2 (OTf = triflate) in CH 3 CN at room temperature regioselectively afforded the alkylidenecyclopentenylated indole 4aa in 99 % yield (Scheme ). The reaction was found to be general for pentafulvenes derived from aromatic aldehydes or ketones and several substituted indoles …”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations